Grey-sided vole and bank vole abundance in old-growth forest patches of different size and connectivity - Paulsson, Niklas (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2011)
Vole populations in northern Scandinavia vary in cycles with peaks every third or fourth year as described by the National Environmental Monitoring Programme of small mammals (NEMP). Some vole species have declined in population numbers since the NEMP started in 1971, especially the grey-sided vole (Myodes rufocanus) which is nearly extinct in the forested region. Since small mammals are an important food source for several avian and mammalian predators, the decline in vole numbers is expected to have consequences for the whole food chain, especially if other vole species start to decline in numbers. This study tried to test the hypothesis that presence and abundance of M. rufocanus (a specialist species) and Myodes glareolus (a generalist species) can be predicted by patch size and connectivity of forest patches >60 years old with a minimum of 15% pine >100years old. I found no dependence on patch size or connectivity for either species, possibly due to too small sample size of forest patches. However, I did find a higher occurrence of M. rufocanus and abundance of M. glareolus in nature forests in this study compared to the situation in managed forests surveyed in the NEMP.